Equity valuation of Sonae SGPS, S.A. - Sousa, Gonçalo José Martins (2021)
The main goal of this project is to estimate the Equity value of Sonae SGPS, S.A. and emit an opinion regarding the market value of its shares. Sonae is one of the biggest Portuguese groups and it contains several different business units. In consequence, it can be considered as an extremely well diversified entity, which makes its equity valuation one of the most complex and challenging among Portuguese companies. Additionally, having into consideration the current pandemic situation, this valuation also constitutes an opportunity to understand the impact of the coronavirus pandemic in the Portuguese economic context, particularly, in Sonae. Regarding the valuation process, firstly, we are going to identify which are the main models and methods that are currently being used to evaluate a company, and, for each one of those models, its advantages and drawbacks are identified. Secondly, we will analyze the group, specifically, identifying all its business units, analyzing how the coronavirus pandemic has affected them, and what are the company’s future perspectives. Additionally, in order to understand better the context in which the group operates, we are going to analyze the main sector in which it is present. Once this analysis is completed, and given the characteristics of the group, it will be chosen which models to apply in order to obtain an accurate and reliable valuation. Based on the results obtained, we are going to emit an opinion regarding the market value of the stock at the end of 2020.